The Effect of Learning Habits and Self - Efficacy towards Students’ English Learning Outcomes - Sukmawati Sukmawati; Bellona Mardhatillah Sabillah (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The success or failure of students in learning can be seen from the results of their studies. If students get good learning outcomes, it can be said that students are successful. This study aimed to determine the existence of (1) the effect of learning habits on English learning outcomes, the effect of self-efficacy on English learning outcomes, and (3) The effect of learning habits and self-efficacy on English learning outcomes. Data were collected by distributing questionnaires and documentation from 30 respondents. Learning habits were measured by a learning habits questionnaire developed by Bakare 1971. The Motivation and Strategy Learning Questionnaire (MSLQ) instrument developed by Pintrich et al in 1991 was used to measure self-efficacy, while student learning outcomes was obtained from formative test scores. This research results showed that there is a positive influence between self-efficacy and learning habits with learning outcomes. This means that the better the Self-Efficacy and learning habits, the higher the Learning Outcomes, and conversely the worse the Self-Efficacy and learning habits, the lower the Learning Outcomes